Validitas Rencana Pembelajaran Semester Mata Kuliah Kimia Dasar Program Studi Pendidikan Biologi Universitas Mahaputra Muhammad Yamin - Afrahamiryano Afrahamiryano (JURNAL EKSAKTA PENDIDIKAN (JEP), 2018)
This research is validation study of Semester Learning Plan of Basic Chemistry. This aims to know the validity of Semester Learning Plan of Basic Chemistry from Biology Education Program of Mahaputra Muhammad Yamin University. Validation is done by using expert consideration method. Instrument used is a questionnaire that has been analyzed using descriptive statistics. Data analysis results show that validity of the designed Basic Chemistry’s Semester Learning Plan is highly valid. To strengthen the results of the analysis, then performed the analysis of validity with the consideration of expert through CVR method. CVR score obtained is ± 1. This show that Basic Chemistry’s Semester Learning Plan is feasible and relevant used in the learning process. So, the conclusion is Basic Chemistry’s Semester Learning Plan is highly valid and can be used in learning process.